Studies on the recently discovered crayfish, Austropotamobius torrentium (Shrank, 1803), in Turkey: morphological analysis and meat yield - Harlioglu, MM; Güner, U (Wiley, 2006)
[Abstract Not Available]
Keywords: meat yield; Austropotamobius torrentium; crayfish; distribution; morphology; Turkey